In the company of women : inspiration and advice from over 100 makers, artists, and entrepreneurs - Bonney, Grace (Artisan, 2016)
"Across the globe, women are embracing the entrepreneurial spirit and starting creative businesses. In the Company of Women profiles over 100 of these influential and creative women from all ages, races, backgrounds, and industries"--Amazon.com.